Occult hepatitis B virus coinfection in HIV‐positive African migrants to the UK: a point prevalence study. Issue 3 (3rd October 2013) - Chadwick, D; Doyle, T; Ellis, S; Price, D; Abbas, I; Valappil, M; Geretti, AM
<x xml:space="preserve">Abstract</x> Objectives Occult (surface antigen‐negative/DNA‐positive) hepatitis B virus (HBV) infection is common in areas of the world where HBV is endemic. The main objectives of this study were to determine the prevalence of occult HBV infection in HIV‐infected African migrants to the UK and to determine factors associated with occult coinfection. Methods This anonymized point‐prevalence study identified Africans attending three HIV clinics, focussing on patients naïve to antiretroviral therapy (ART). Stored blood samples were tested for HBV DNA. Prevalence was calculated in the entire cohort, as well as in subpopulations. Risk factors for occult HBV coinfection were identified using logistic regression analysis. Results Among 335 HIV‐positive African migrants, the prevalence of occult HBV coinfection was 4.5% [95% confidence interval (CI) 2.8–7.4%] overall, and 6.5% (95% CI 3.9–10.6%) and 0.8% (95% CI 0.2–4.6%) in ART‐naïve and ART‐experienced patients, respectively. Among ART‐naïve anti‐HBV core (anti‐HBc)‐positive patients, the prevalence was 16.4% (95% CI 8.3–25.6%). The strongest predictor of occult coinfection was anti‐HBc positivity [odds ratio (OR) 7.4; 95% CI 2.0–27.6]. Median HBV DNA and ALT levels were 54 IU/mL [interquartile range (IQR) 33–513 IU/mL] and 22 U/L (IQR 13–27 U/L), respectively. Conclusions Occult HBV coinfection remains under‐diagnosed in African HIV‐infected patients in the UK. Given the range of HBV DNA levels observed, further studies are warranted to determine its clinical significance and to guide screening strategies and ART selection in these patients.